Exploring the Impact of Sports Participation on the Health Aspect of Women Athletes (International Journal of Food and Nutritional Sciences, 2022)
The relationship between sports participation and the health outcomes of women athletes is intricate and multifaceted, influenced by factors like the type of sport, competition level, individual traits, and sociocultural context. This research aims to identify the key health domains of female athletes which have been significantly impacted by their participation in sports. By using secondary literature, the present paper could identify a few specific health domains of female athletes such as their physical fitness, mental health, lifestyle choices, and overall quality of life and explore the impact of their sports participation on it. Further, the present research intends to provide insights into the unique health challenges female athletes face due to their participation. The findings of the study underline the multifaceted benefits of sports participation for female athletes, encompassing improvements in their physical health, mental well-being, social outcomes, subjective well-being, self-esteem, and body image. These results show the positive impact of sports engagement on women athletes' overall health and holistic development.